The effect of Gable angle size and spring activation distance of 0.016 x 0.022 NiTi and TMA sectional T-loop towards force, moment y and moment z values - Wachyudi, Norman; Hambali, Tono S.; Salim, Jono; Mardiati, Endah (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
This study was carried out to find the effects of angle of Gable bends and amount of activations of 0.016 x 0.022 inch NiTi and TMA sectional T-loop springs to the force moment and moment delivered. The design of the research is true in-vitro laboratory experimental design, to measure the force, moment. and moments, an axial moment device was designed purposely. The samples were 30 springs comprised of 15 NiTi and 15 TMA with variations of Gable bends 0Ë-0Ë, 10Ë-10Ë, and 20Ë-20Ë Force, moment and moments were measured at 1, 2, and 3 mm amount of activations. Data was tested statistically using the ANAVA with 3x2x3 factorial designs and 5 replications for each all. The results showed that angle of Gable bends, amount of activations and type of wires significantly affect the force and moments delivered, but the angle of Gable bends significantly affect moment. It could be concluded that the greater angle of Gable bends will produce the greater force and moments. The greater amount of activations will produce the greater force and moments.